Teknologi Subtitusi Bahan Dalam Pengembangan Usaha Mikro Pakan Organik Berprotein - Dumasari Dumasari (UII, 2014)
This article aims to review the urgency of the use technology substitution of materials inthe development of micro enterprises organic feed with protein. Existence of microenterprises organic feed with protein have economic value, social, and environmental forefforts to empower peasants. With the technology of substitution of materials, microenterprises can contribute to the improvement of peasants income. Ingredients by proteinorganic feed derived from various types of agricultural waste. This type of enterprises is alsopotentially reduce the economic burden of peasants because it is easier to feed for fresh waterfish with a low cost.